Report on industrial attachment with Sanchoon Builders Pte Ltd - Chan, Sau Choy. (2008)
The author was attached to Sanchoon Builders Pte Ltd at the Jalan Besar Stadium site and was involved in the construction of the Main and Minor Grandstand, the Multi-storey Carpark and the Swimming Pool.